A theory of creative society in the format of political manifestation - Matsevich-Dukhan, Iryna Ja. (Journal of the Belarusian State University. Sociology, 2019)
The article reveals prerequisites for the formation of the creative society theory in the XXIst century. Different approaches to its elaboration are subjected to discussion. The author analyses conceptions on the basis of which the political programme «Creative Europe» (2014–2020) is fulfilled. The political challenges of its employment in the Eastern Partnership countries are indicated.
Keywords: creative society theory; creative society; creative economy; creative industry; lifestyle; art; art market